Metal Reduction by Methobactins - Swanson, Teresa; Casper, Elisabeth; Chesner, Lisa (My University, 2010)
Methanobactins (mb) are copper-binding peptides or chalkophores secreted by methanotrophs to scavenge copper ions from the environment. A unique feature of these molecules is their ability to reduce and stabilize copper as Cu(I). In the absence of Cu, the molecule will also bind and reduce many other metals including silver, gold and mercury. We have investigated the methanobactin (MB) from Methylosinus trichosporium OB3b, as well as a newly isolated methanobactin from Methylocystis sp. SB2 in order to determine how these novel polypeptides reduce and stabilize Cu(I) and other metals.
Color poster with text, diagrams, and tables.
Keywords: Methanobactin; Copper--Effect of chemicals on; Reduction (Chemistry); Posters